2007
DOI: 10.1111/j.1365-3156.2006.01789.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of artesunate, artemether and amodiaquine susceptibility and molecular analysis of putative resistance‐associated mutations of Plasmodium falciparum from São Tomé and Príncipe

Abstract: Summaryobjective To evaluate the basal in vitro responses of Plasmodium falciparum isolates collected in The Democratic Republic of Sã o Tomé and Príncipe to artemether (ATH), artesunate (ATN) and amodiaquine (AMQ).methods The prevalence of given single nucleotide polymorphisms in the pfmdr1, pfcrt, pftctp and pfATPase6 genes 1 was assessed by PCR-RFLP or DNA sequencing, and gene copy numbers were estimated by real-time PCR.results Mean IC50s to ATH and ATN were relatively low (1.12 nm and 0.58 nm, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 20 publications
8
38
1
Order By: Relevance
“…The IC 50 values obtained for artemisinin against Amazonian field isolates exhibited low variation (average IC 50 = 2.1 ± 1.0 nM). Given the number of samples studied, the levels of sensitivity of Amazonian P. falciparum field isolates to artemisinin are in agreement with results for other field isolates reported in the literature (Jambou et al 2005, Ferreira et al 2007, Gama et al 2011). In Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The IC 50 values obtained for artemisinin against Amazonian field isolates exhibited low variation (average IC 50 = 2.1 ± 1.0 nM). Given the number of samples studied, the levels of sensitivity of Amazonian P. falciparum field isolates to artemisinin are in agreement with results for other field isolates reported in the literature (Jambou et al 2005, Ferreira et al 2007, Gama et al 2011). In Fig.…”
Section: Resultssupporting
confidence: 75%
“…However, two samples revealed high IC 50 values (224 and 259 nM) that were lower than the in vitro threshold value for quinine resistance (500 nM) established by the WHO (2007). The levels of field isolate parasite inhibition (IC 50 = 2.1 ± 1.0 nM) by artemisinin are generally in agreement with data from other parts of South America and Brazil (Jambou et al 2005, Ferreira et al 2007. The drug susceptibility of field isolates was evaluated as a means to characterise the resistance profiles of the samples of Amazonian parasites utilised to evaluate their susceptibility to infusions.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These point mutations are new compared to the data available on the polymorphism in PfATPase6 gene. Similar studies were conducted in Sao Tome and Principe and showed a silent mutation of T2694A (Ferreira et al, 2007). Ferreira et al (2008) also published a similar paper with Brazilian samples (Ferreira et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…IC 50 values observed in many studies from South America appear to be similar to those observed in Africa and different from those in SE-Asia, where chemotolerance appears to be higher. As an example, a recent study from Laos has reported an IC 50 to Artesunate of 5.0 nm among local P. falciparum populations, a value that is more than fivefold higher than the one observed in Brazil (0.85 nm) by Ferreira et al [109,110]. In contrast, African parasites appear to be more susceptible to ART derivatives with IC 50 s to Artesunate of 0.58, 0.73 and 2.2 nm from Sao Tome, Gabon and Senegal, respectively [109,111].…”
Section: Pfatpase6 and Mechanism Of Action Of Artemisinin Resistancementioning
confidence: 80%